2022
DOI: 10.3390/molecules27103047
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Decreases the Invasion Potential of Gastric Cancer Cells

Abstract: The cancer-preventive agent Resveratrol (RSV) [3,5,4′-trihydroxytrans-stilbene] is a widely recognized antioxidant molecule with antitumoral potential against several types of cancers, including prostate, hepatic, breast, skin, colorectal, and pancreatic. Herein, we studied the effect of RSV on the cell viability and invasion potential of gastric cancer cells. AGS and MKN45 cells were treated with different doses of RSV (0–200 μM) for 24 h. Cell viability was determined using the Sulphorhodamine B dye (SRB) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Although the exact mechanism of action has not been fully defined yet, resveratrol induced cell senescence, cell cycle arrest, and increased anti-oxidant capacity ( Rojo et al, 2022 ) (decreased the invasion) as well as reducing metastasis in former preclinical studies ( Pyo et al, 2020 ). However, its biological effects might vary considering different cell types ( Farhadnejad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mechanism of action has not been fully defined yet, resveratrol induced cell senescence, cell cycle arrest, and increased anti-oxidant capacity ( Rojo et al, 2022 ) (decreased the invasion) as well as reducing metastasis in former preclinical studies ( Pyo et al, 2020 ). However, its biological effects might vary considering different cell types ( Farhadnejad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The promising advantage of resveratrol on preventing AGS cells invasion and metastasis was stated in-vitro , especially at the concentrations of 5–25 µM ( Rojo et al, 2022 ). Almost similarly, the current experiment proved a reduction in cells migration following treatment of AGS cells with cisplatin-resveratrol combination, at all concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This pathophysiological status is alleviated by RSV owing to its ability to relieve inflammation, inhibit oxidative damage, and prevent apoptosis. Furthermore, previous studies have demonstrated that RSV suppresses the inflammatory response in SCI by upregulating the SIRT-1 signaling pathway and downregulating the NF-κB signaling pathways ( 36 , 37 ). SCI is associated with the generation of free radicals, which cause oxidative degradation of lipids ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Rojo et al have demonstrated that RES administered at doses ranging from 5 to 25 µM can enhance superoxide dismutase (SOD) activity, while concurrently suppressing NF-κB transcriptional activity and heparanase activity in gastric cancer cells (AGS and MKN45). This finding suggests that RES may have a role in reducing the invasive potential of gastric cancer cells [66]. Furthermore, Buhrmann et al reported that RES can downregulate TNF-β-induced colorectal cancer cell (HCT116) proliferation by blocking TNF-β/TNF-β-receptor-induced NF-κB activation, resulting in activation of caspase-3 cleavage [67].…”
Section: In Vitro Studies Of Resveratrol On Anticancer Activitymentioning
confidence: 97%